Korelasi Nilai HbA1c dengan Kadar Kolesterol Total pada Pasien Diabetes Mellitus Tipe 2 - Ayu Sabrina Susilo; Zulfian Zulfian; Ika Artini (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background of the study: Diabetes mellitus (DM) is a chronic metabolic disease due to pancreatic β cells that having decreased insulin production, or when insulin in the body experiencing ineffectiveness. Based on IDF data, in 2015 the number of DM sufferers in Indonesia is 9.1 million, and it expected will continue to increase in 2035 with a total of 14.1 million. With these data, Indonesia ranked 5th of DM sufferers in the world. Purpose: To determine the correlation between the HbA1c value and total cholesterol levels in type 2 DM patients at Pertamina Bintang Amin Hospital in Bandar Lampung in 2019. Research Method: This research design is correlative analytic with the cross-sectional method using purposive sampling as many as 48 samples of type 2 DM patients who match with the inclusion criteria. Data collecting begins in January-February 2020. The data on this research used secondary data in the form of medical records. After the data collected, data will be evaluated by the Spearman test. Research Results: In this study, the sample obtained 48 patients with type 2 DM with a HbA1c value of ≥9%, as many as 30 patients (62.5%), for a HbA1c value <9% ie as many as 18 patients (37.5% ) and total cholesterol level ≥200mg / dl as many as 29 patients (60.4%), for total cholesterol levels <200mg / dl as many as 19 patients (39.6%). Spearman correlation results obtained p-value = 0.030 and r = + 0.314, because of the value of p = 0.030 <0.05 so that it can be declared Ha accepted and Ho declared rejected or there is a significant correlation, with r = 0.314 it can be interpreted that the strength of the correlation is positive between HbA1c value with total cholesterol level in type 2 DM patients. Conclusion: This study concludes there is a significant correlation between HbA1c value and total cholesterol level in type 2 DM patients with p-value = 0.030.